DRP (DRUG RELATED PROBLEM) MENURUT KLASIFIKASI CIPOLLE PADA PENYAKIT CKD (CHRONIC KIDNEY DISEASE) + PNEUMONIA - Hohiyando Sitompul; Jefri Siswanto Buulolo; Miratun Sopiah Ritonga; Qomariah Ritonga; Wina Rizky Octavia; Yelli Simarmata (Jurnal Kesehatan Sejahtera, 2025)
Drug Related Problem (DRP) is a significant issue in clinical practice that can have a serious impact on patient outcomes, especially in complex cases with comorbidities. This study aims to identify and classify DRP according to the Cipolle Classification in patients with Chronic Kidney Disease (CKD) and pneumonia in the hospital (hospital name, if any). The design of this study is descriptive observational with retrospective data collection from medical records of CKD patients who were also diagnosed with pneumonia during the period (eg) January 2023 - December 2024. The study sample involved (number of samples) patients who met the inclusion and exclusion criteria. DRP data will be identified from medical records, including treatment history, laboratory results, and medical records, then classified using the Cipolle system, which includes DRPs such as the need for additional drugs, ineffective drugs, too low doses, too high doses, drug side effects, drug interactions, and non-compliance. The expected results show the prevalence and specific types of DRPs that most often occur in this patient population, with a focus on drug interactions and drug dose adjustments due to decreased kidney function. This study is expected to provide important information for health workers, especially clinical pharmacists, to optimize drug therapy, minimize the risk of DRP, and improve the quality of life of CKD patients with pneumonia complications.